Current control strategy of grid-connected inverter for distributed generation under nonliner load conditions - Naderipour, Amirreza (2017)
Distributed generation (DG) has become more important in recent years for supplementing traditional fossil energy resources for power generation. The DGs include microturbine (MT), fuel cell, photovoltaic (PV) arrays, wind turbine and storage devices. The DG units can operate in parallel to the main grid or in a microgrid (MG) mode. The MG is a discrete energy system consisting of DG and loads that are capable of operating in parallel with, or independently from the main grid. Meanwhile, Grid-Connected Inverters (GCIs) are typically used as the interfaces to connect each DG to the common bus in an MG mode. In the ongoing effort to improve the performance of MG, control strategy of three-phase GCI under nonlinear load conditions has become a mature and well-developed research topic, and some control strategies have been implemented in several countries. A new approach is proposed to control the GCI of DG in an MG under nonlinear and unbalanced load conditions. The proposed control strategy features the synchronous reference frame method. The primary advantage of this method is its ability to effectively compensate for the harmonic current content of the system currents and MG without using any compensation devices, such as an Active Power Filter (APF) or passive filter. In this system, the control strategy is designed to eliminate the main harmonics as well as to cancel the remaining harmonics. Furthermore, correction of the system unbalance is another key feature of the proposed strategy. Fast dynamic response, simple design, stability, and fast transient response are other key features of the presented strategy. The current total harmonic distortions were reduced from above 37.8% to less than 1% with the proposed control strategy under nonlinear load conditions. The proposed control method can be used on the GCI of MT and PV; and has the ability to reduce the complexity, size and cost of the control method in comparison with APFs.